The Influence of Family Communication Patterns on Parenting Agreements for Children with Special Needs - Resman Muharul Tambunan; Des Hanafi; Fachmi Ibrahim (LONTAR: Jurnal Ilmu Komunikasi, 2024)
Children with special needs show their own uniqueness and challenges in parenting. Caring for children with special needs requires creating meaning and cooperation among family members. Family communication patterns have a significant impact on how arrangements for caring for children with special needs are formed and implemented. The importance of family communication patterns in the context of parenting agreements for children with special needs cannot be ignored. The relationship between parents and children is the core interaction in the family system. This research aims to explore the influence of family communication patterns on parenting agreements for children with special needs. This research was designed using a descriptive causality survey method with a quantitative approach with a positivism paradigm to test research hypotheses and descriptive analysis, by collecting data from relevant respondents using a digital questionnaire. The results of the significance and hypothesis tests show that the protective and laissez faire variables have a significant value with H0 being accepted, while pluralistic and consensual have an insignificant value with H0 being rejected.